2020
DOI: 10.4067/s0717-95022020000601597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatigue Load on Internal Mechanical Properties of the Intervertebral Disc

Abstract: Lumbar disc herniation is considered to be the main pathological factor for the common clinical disease of low back pain. Biomechanical factor is an important cause of lumbar disc herniation, so it is urgent to analyze the stress/strain behavior of intervertebral disc under different loading condition. Slow repetitive loading is considered to be an important factor of spine and disc injuries, and the effect of fatigue load on internal displacement in the intervertebral disc was investigated by applying the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Overall, the axial displacement of superficial AF is greater than that of deep AF. This is consistent with the findings of Liu et al (2020), who studied the effect of fatigue loading on the internal displacement of the disc by applying the optimized digital image correlation technique and found that the axial displacement of the superficial AF was the greatest before fatigue loading. Meakin et al (2000) measured the displacement of the internal marker points of the nucleus pulposus discectomy with the interactive image analysis software, and concluded that when the nucleus pulposus discectomy is subjected to compressive load, the outer edge of the fibrous ring deforms outward, which is consistent with the phenomenon we observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the axial displacement of superficial AF is greater than that of deep AF. This is consistent with the findings of Liu et al (2020), who studied the effect of fatigue loading on the internal displacement of the disc by applying the optimized digital image correlation technique and found that the axial displacement of the superficial AF was the greatest before fatigue loading. Meakin et al (2000) measured the displacement of the internal marker points of the nucleus pulposus discectomy with the interactive image analysis software, and concluded that when the nucleus pulposus discectomy is subjected to compressive load, the outer edge of the fibrous ring deforms outward, which is consistent with the phenomenon we observed.…”
Section: Discussionsupporting
confidence: 91%
“…The internal displacement was measured by optimized DIC technology (Liu et al, 2020), the intervertebral disc was cut along the sagittal plane, and the iron oxide nanoparticles were evenly coated on the incision surface as a marker point to record the deformation of different areas of the intervertebral disc. A pair of marked points a1 (x1, y1) and a2 (x2, y2) with similar x value were selected, and the axial displacement distribution will be reflected by comparing the y value between this pair of points before and after loading.…”
Section: Methodsmentioning
confidence: 99%